Immediate effect of foam roller on pain and ankle range of motion in patients with plantar fasciitis: A randomized controlled trial - Aishwarya R. Ranbhor; Ashish J. Prabhakar; Charu Eapen (World Scientific Publishing, 2021)
Background: Stretching has been proven to be effective on pain and range of motion (ROM) in patients with plantar fasciitis. Despite recent gain in popularity and the proposed theories of effectiveness of foam roller, there is a lack of literature on the effect of foam rolling on plantar fasciitis. Objective: The objective of this study was to compare the effects of foam rolling and stretching on pain and ankle ROM in patients with plantar fasciitis. Methods: A total of 50 participants were included and randomly allocated to the stretching and foam roller groups. Visual analog scale (VAS), pressure pain thresholds (PPTs) for gastrocnemius, soleus and plantar fascia and weight-bearing lunge test (WBLT) measurements were recorded at baseline and immediately after treatment. Results: Within-group analysis has shown there is a statistically significant difference (p<0.001) in all the outcome measures in both foam roller and self-stretching groups. The between-groups analysis showed no statistical significance difference in VAS, plantar fascia PPT and WBLT parameters (with p-values of 0.171, 0.372 and 0.861, respectively); however, significant differences were found in gastrocnemius PPT (p=0.029) and soleus PPT (p=0.013). Conclusion: It was seen that both stretching and foam rolling techniques helped in reducing pain and increasing the ROM. However, the effectiveness of foam roller was superior to stretching in terms of increase in PPTs at gastrocnemius and soleus. Clinical Trial Registration No: CTRI/2018/01/011398. Name of registry: The Clinical Trials Registry - India (CTRI); https://ctri.nic.in.